2016
DOI: 10.3892/ijmm.2016.2671
|View full text |Cite
|
Sign up to set email alerts
|

piR-651 promotes tumor formation in non-small cell lung carcinoma through the upregulation of cyclin D1 and CDK4

Abstract: Piwi-interacting RNAs (piRNAs or piRs) are a novel class of non-coding RNAs that participate in germline development by silencing transposable elements and regulating gene expression. To date, the association between piRNAs and non‑small cell lung carcinoma (NSCLC) has not yet been elucidated. In the present study, we have demonstrated that a significant increase in piR-651 expression occurs in NSCLC. Furthermore, the abnormal expression of piR-651 was associated with cancer progression in the patients with NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 28 publications
1
63
0
Order By: Relevance
“…The expression of piR651 significantly increases in non-small cell lung carcinoma [26] and piRNA823 is overexpressed in multiple myeloma patients [27]. Hence, it is possible that HIWI2-associated piRNAs might also be altered in RB and could play a role in the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of piR651 significantly increases in non-small cell lung carcinoma [26] and piRNA823 is overexpressed in multiple myeloma patients [27]. Hence, it is possible that HIWI2-associated piRNAs might also be altered in RB and could play a role in the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A specific piRNA-651 has been demonstrated to be aberrantly overexpressed in various tumors compared with in wild-type tissues (58,59). In NSCLC, a significant increase in piRNA-651 levels was identified to be associated with cancer progression (58).…”
Section: Piwi-pirna In Cancer Developmentmentioning
confidence: 99%
“…A specific piRNA-651 has been demonstrated to be aberrantly overexpressed in various tumors compared with in wild-type tissues (58,59). In NSCLC, a significant increase in piRNA-651 levels was identified to be associated with cancer progression (58). Furthermore, the upregulation of piRNA-651 in A549 lung cancer cells caused a significant increase in cell viability and metastasis, and was associated with the upregulation of cyclin D1 and CDK4 in vivo and in vitro .…”
Section: Piwi-pirna In Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, aberrant expression of piRNAs has been documented in cancers such as breast, pancreas, lung, kidney, colorectal, cervical, head, neck, and gastric cancer . However, only a few piRNAs such as piR‐651, piR‐20365, piR‐021285, piR‐932, and piR‐823 have been intensively explored and validated in different cancers to decipher their role in oncogenesis . Cheng et al reported that the expression of piR‐823 in gastric cancer tissues was significantly lower compared to non‐cancerous tissues and its increased expression inhibited growth of gastric cancer cells .…”
Section: Introductionmentioning
confidence: 99%